Parental leave policies and child care time in couples after childbirth - Pia S. Schober (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This research explores how different parental leave reforms in West Germany impacted on the time mothers and fathers in couples spent on child care. I investigate indirect effects through mothers' labor market return decisions more in detail than previous studies and also examine potential direct associations of reforms of the leave period and benefits with maternal and paternal care time. The analysis uses multilevel multiprocess models for 1299 couples with a first or second birth based on data from the German Socio-Economic Panel (1984-2009). I estimate simultaneously the timing and extent of mothers' labor market return, selection into childbearing, and maternal and paternal child care time over the years following a first or second birth. The findings suggest that the extensions of the maximum period of low-paid or unpaid leave between 1986 and 1992 and the introduction of shorter well-paid leave and two 'daddy months' in 2007 indirectly affected maternal and paternal child care through changes in mothers' work return decisions. Even after controlling for these indirect effects and fathers' take-up of leave, the parental leave extensions were directly associated with longer maternal care time on weekdays, whereas father involvement in child care increased after the 2007 reform.
Keywords: 330; child care; gender division of unpaid work; maternal employment; parental leave policy; parenting; Elternzeit; Kinderbetreuung; Mütter; Väter; Arbeitsangebot; Deutschland